La neuropsichiatria dell’infanzia e dell’adolescenza: l’annullamento del bambino e del ragazzo come soggetti psichici - Giorgini, Luca (Il sogno della farfalla, 2023)
The aim of this paper is to propose an analysis on the current state of child and adolescence neuropsychiatry in Italy, which appears to be strongly defined by an annulment of children and adolescents’ mental reality. In this regards, Fagioli’s theoretical work which postulates the existence of an original Self since birth, allows to clinically and nosologically reevaluate this discipline, laying the foundation for a radical transformation in terms of diagnosis, therapy, and prognosis.